Science Literacy Profile of High School Students as A Basis for Ethnoscience Integration in Learning - Weni Rahmawanti; Wasis Wasis; Hasan Subekti (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to analyze the scientific literacy profile of high school students in physics using the PISA 2025 framework, focusing on identifying strengths and weaknesses in each competency dimension as a basis for developing ethnoscience-integrated learning. Methodology: This study employed a quantitative survey with a diagnostic approach using a science literacy test adapted from the PISA 2025 framework. The instrument consisted of 20 multiple-choice items. Data were collected online and analyzed using descriptive statistics and Benchmark Reference Assessment (PAP). Sampling used simple random sampling on grade XI students. Main Findings: The results show that students’ scientific literacy is in the moderate to low category with uneven competency distribution. Students performed better in explaining scientific phenomena but showed low achievement in designing investigations, evaluating evidence, and interpreting data. Scores ranged from 25 to 85, with an average of 55.07, indicating limited higher-order thinking skills. Novelty/Originality of this study: This study provides an updated empirical mapping of students’ scientific literacy using the PISA 2025 framework, which is still rarely applied. It offers a diagnostic basis for integrating ethnoscience in learning, emphasizing the development of higher-order thinking and contextual understanding aligned with students’ cultural environments.